Immunohistochemical features of benign endometrial hyperplasia in premenopausal women - Н. М. Рожковська; І. С. Ломакіна (Publishing House TRILIST, 2020)
Hyperproliferative diseases of the endometrium play an important role in the structure of gynecological pathology, which are a spectrum of irregular morphological changes. Particularly difficult is evaluation of the phenotypic characteristics of the endometrium hyperplastic processes (EHP) in premenopausal women in the presence of an unstable menstrual cycle. Diagnosis and EHP prognosis remains a difficult task given that it can occur as focal or diffuse lesions with various structural and cytological differences. Objective of the study: to evaluate the immunohistochemical features (phenotypic variants) of benign endometrial hyperplasia in premenopausal women. Material and methods. 33 premenopausal women with abnormal uterine bleeding and verified benign endometrial hyperplasia were examined. Expression of the α-receptors for estrogens type 1 (ER1), progesterone receptors and Ki-67 nuclear protein in the endometrium stroma and glands was analyzed. Micromorphometry was performed and the D-score was calculated. Results. Prevalence of comorbid lesions in patients was the combination of endometrial hyperplasia and fibroids (51.4%), cases of abnormal uterine bleedings against submucosal fibroids (13.5%), endometrial polyps (8.1%), combinations of EHP and peritoneal endometriosis (10.8%), adenomyosis and myoma (8.1%), or other combinations of endometrial and myometrial proliferative pathology. D-score for surgery averaged 1.78 ± 0.11 indicating a low risk of malignancy. There were changes after treatment in the quantitative presentation of the studied proteins in stroma and endometrial glands. Thus, before treatment in the glands was determined up to 100% of cells containing ER1 in large quantities, while after treatment their number decreased by an average of 20%. Similar dynamics was observed with progesterone receptors activity. Conclusions. The main prognostic significant phenotypes of endometrial proliferative pathology have been identified. After removing of pathologically chanced endometrium and subsequent treatment with dydrogesterone during 6 months there is prognostically positive decreasing in the ER1 density as well as the Ki-67 protein expression